2017
DOI: 10.1016/j.imr.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of acupotomy for lumbar disc herniation: a study protocol for a randomized, assessor-blinded, controlled pilot trial

Abstract: BackgroundAcupotomy aims to reduce pressure on the nerve, improve surrounding blood circulation, and recover the kinetic state of soft tissue in treating lumbar disc herniation. Although several previous studies have suggested the potential use and substantial benefits of acupotomy, there is still insufficient evidence regarding this technique. This trial is designed to determine if acupotomy is more effective than manual acupuncture in improving low back pain and/or leg pain, disability, lumbar mobility, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…The study protocol has been previously published [ 18 ]. In summary, 50 participants with symptomatic LDH were recruited to this randomized, two parallel-armed, controlled, assessor-blinded, single center, pilot clinical trial.…”
Section: Methodsmentioning
confidence: 99%
“…The study protocol has been previously published [ 18 ]. In summary, 50 participants with symptomatic LDH were recruited to this randomized, two parallel-armed, controlled, assessor-blinded, single center, pilot clinical trial.…”
Section: Methodsmentioning
confidence: 99%
“…Based on what we know so far, we have found some limitations of this Protocol:(1)Most of the sites included in the study are in China; (2)The application of moxibustion in other countries and regions needs further study. (3)At the same time, the differences of moxibustion operation methods between different countries should also need be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar disc herniation (LDH) is a clinically common degenerative spinal disease, which adversely affects patients' quality of life and work ability [1] .The clinical symptoms of the disease are localized low back pain or lower extremity radioactive neuralgia, which is distributed in a region corresponding to the dermal nodes of the associated nerve roots [2] ,LDH mainly affects 1-3% of the general population, and most of the patients are aged 30-50 years old. Meanwhile, the common lesion site of LDH is the lumbar disc between L4/L5 and L5/S1, which has become a common occupational health problem and brought severe test to the medical security system [3] .The treatment of LDH includes surgery and conservative modalities, nowadays, more and more attention has been paid to conservative treatment, One study showed that less than 2% of patients with low back pain receive LDH surgery [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Lumbar disc herniation (LDH) is one of the most common degenerative spinal disorders in young and middle-aged patients. [ 1 ] LDH is highly prevalent among patients aged 30 to 50 years, and approximately 95% of lumbar disc herniations occur at the L4/L5 and L5/S1 levels. [ 2 ] The main symptoms of LDH include lower back pain, radiation pain on one side or in the lower extremities, weakening of muscle strength, and sensory disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 , 23 ] In the treatment of lumbar disc herniation, the role of acupotomy is to reduce nerve pressure, improve peripheral blood circulation, and restore the kinetic state of soft tissue. [ 1 , 24 ]…”
Section: Introductionmentioning
confidence: 99%